Formação de trabalhadoras: o programa mulheres mil sob o olhar de suas educadoras - Silva, Cleonice Maria da (2015)
This paper presents the results of a master‟s degree research with the subject of the “Thousand Women Program” developed by the Brazilian Federal Government in partnership with the Federal Institutions of Vocational and Technological Education. The investigative approach had qualitative basis. It was conducted in the form of a case study and developed in the municipality of Inconfidentes in Minas Gerais, Brazil. The objectives were to: i) discuss the pedagogical proposal of professional training/qualification of women workers participants of the Thousand Women Program; ii) characterize the program and identify its educational concepts; iii) understand how the training proposal of the Thousand Women Program was developed, by analyzing national program documents and reports obtained from the teachers; iv) understand the formation processes, which aimed to recognize the knowledge arising from life course, labor and women's experience. In the methodological course of this research, a literature review was conducted using national journals. We also used dissertation and thesis summaries, as well as electronic documents available on the website of the Ministry of Education and Ministry of Social Development and Hunger Alleviation - Secretariat of Vocational and Technological Education - SETEC, and National Secretariat of Policies for Women and the Gender Observatory. Semi-structured interviews were performed with the educators of the program to complement the information.